Strategic analytics the insights you need from Harvard Business Review - Ross, Jonathan Todd (Gildan Audio, 2020)
Data analytics offer an incredible opportunity to predict the future, engage with new technological advancements, and gain valuable insights about your business. But unless you're staying on top of the cutting edge of analytics, your company is wasting that potential-and your competitors will be gaining speed while you fall behind. These articles by experts and consultants will help you understand today's essential thinking about what data analytics are capable of and how to adopt their use in your organization. This book will help you kick off urgent conversations, focus on the right initiatives in your company, and capitalize on the opportunity of analytics.Get up to speed and deepen your understanding of the topics that are shaping your company's future with the Insights You Need from Harvard Business Review series. Featuring HBR's smartest thinking on fast-moving issues-blockchain, cybersecurity, AI, and more-each book provides the foundational introduction and practical case studies your organization needs to compete today and collects the best research, interviews, and analysis to get it ready for tomorrow. You can't afford to ignore how these issues will transform the landscape of business and society. The Insights You Need series will help you grasp these critical ideas-and prepare you and your company for the future.
Downloadable audio file
Keywords: Business; Affaires; businesses (business enterprises); BUSINESS & ECONOMICS / General; Downloadable audio books; Audiobooks; Livres audio